The Effect of Inquiry - Based on Science Technology and Society Methods to the social Learning Outcomes. - Yani Suryani (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2017)
The background of this research is the issue of globalization that impact on society's lives, especially school-age children (students) who started to use the technology in every activity. The problem in this study is whether the method of inquiry – based on Science Technology and Society has a significant effect on social science learning outcomes of students in SMPN 1 Bandung. This study use quasi-experimental approach, with nonequivalent (pretest and posttest) the Control Group Design. The average result of experimental class’ pre-test is 59.72, and the post-test average is 77.08, the gain is 0, 46, While in the control classroom the average of pre - test is 56.81, and the post-test is 68.75, and the gain is 0, 28. There seems to be a significant improvement between the experimental class and the control class. The results were analyzed using the data analysis software called SPSS 16 for windows shows the sig is 0.000 < α 0.05, which means the test results showed that Ho strongly rejected, means that there are some learning outcomes distinctions between the student who get a method of inquiry -based learning with Science Technology and Society Methods with those who received conventional learning at the post-test. Post-test results of the students who received inquiry -based learning with the Science Technology and Society Methods is better than the students who received conventional learning. It can be seen from the motivation to learn, learner inquiry frequency, the students learning outcomes in land use and settlement patterns material based on the physical condition of the earth's surface. The recommendations were based on the research findings and the discussion of the effect of the use of inquiry -based science technology society method. It is expected that schools, Social Sciences’ MGMP, social science Teacher and the next researcher can use and develop the inquiry -based science learning technology methods community in the social science.